2009
DOI: 10.1002/cphc.200800663
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensing of Serine and Tyrosine with Aligned CdS Nanowire Arrays Based on pH‐Dependent Photoluminescence Behavior

Abstract: The differential sensing of tyrosine and serine is achieved with well-aligned CdS nanowire arrays by exploring the pH-dependent photoluminescence behavior of the nanowire arrays toward exposure to the two amino acid solutions. The contrasting trend in photoluminescence (PL) intensity with respect to variations in analyte concentration observed at pH 11 served as the check point for the present differential sensing. The application format of the nanowire array is better suited for further sensing device assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In particular, doping with small amounts of noble metals can affect the crystallization progress of semiconductors. 3 As one of the most important II-VI semiconductors, CdS has already shown promise in a broad range of biomedical applications such as sensing for ionic species 4,5 and biomolecules 6 because it exhibits superior photoluminescence properties to conventional organic dyes. In recent years, doping of CdS nanostructures has inspired a great deal of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, doping with small amounts of noble metals can affect the crystallization progress of semiconductors. 3 As one of the most important II-VI semiconductors, CdS has already shown promise in a broad range of biomedical applications such as sensing for ionic species 4,5 and biomolecules 6 because it exhibits superior photoluminescence properties to conventional organic dyes. In recent years, doping of CdS nanostructures has inspired a great deal of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Its valence band at relatively negative potential offers CdS good photocatalytic activities . Furthermore, the photoluminescence (PL) property of CdS has been explored for sensing toward a number of ionic species and biomolecules . We previously showed that ethylenediamine (EN)-capped CdS nanowires (NWs) can selectively detect Ag + and Cu 2+ among 12 biologically relevant metal ions .…”
Section: Introductionmentioning
confidence: 99%